2015
DOI: 10.1128/aem.00868-15
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Avermectin Production in Streptomyces avermitilis by Manipulating the Expression of a Novel TetR-Family Regulator and Its Target Gene Product

Abstract: Avermectins produced by Streptomyces avermitilis are commercially important anthelmintic agents. The detailed regulatory mechanisms of avermectin biosynthesis remain unclear. Here, we identified SAV3619, a TetR-family transcriptional regulator designated AveT, to be an activator for both avermectin production and morphological differentiation in S. avermitilis. AveT was shown to indirectly stimulate avermectin production by affecting transcription of the cluster-situated activator gene aveR. AveT directly repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 47 publications
0
40
0
2
Order By: Relevance
“…The biosynthetic genes of antibiotics are generally clustered together on chromosomes or plasmids (31, 32) and usually contain one or more CSRs (33) that provide a direct contributions to antibiotic production through transcriptional regulation of other biosynthetic genes in the clusters (18,34). In the present study, we identified and characterized LmbU, a novel transcriptional regulator that is involved in the regulation of lincomycin biosynthesis.…”
Section: Discussionmentioning
confidence: 87%
“…The biosynthetic genes of antibiotics are generally clustered together on chromosomes or plasmids (31, 32) and usually contain one or more CSRs (33) that provide a direct contributions to antibiotic production through transcriptional regulation of other biosynthetic genes in the clusters (18,34). In the present study, we identified and characterized LmbU, a novel transcriptional regulator that is involved in the regulation of lincomycin biosynthesis.…”
Section: Discussionmentioning
confidence: 87%
“…We reported that PhoP, the response regulator of the two‐component PhoR‐PhoP system that responds to phosphate limitation, directly inhibits avermectin production by binding to the PHO box in the aveR promoter (Yang et al ., ). Some characterized regulators shown to control avermectin biosynthesis through indirect effects on aveR transcription are AveI (Chen et al ., ), SAV7471 (Liu et al ., ), SAV576 (Guo et al ., ), SAV151 (He et al ., ), SAV577 (Guo et al ., ), AveT (Liu et al ., ) and extracytoplasmic function (ECF) σ 25 (Luo et al ., ). To date, no other regulators have been reported to directly regulate avermectin production via aveR .…”
Section: Introductionmentioning
confidence: 97%
“…Sputcn32_0304, the second response regulator in the three-component regulatory system, has a predicted effector domain with a helix-turn-helix (HTH) motif that is essentially similar to the HTH domains in the LuxR/GerE family transcriptional regulators. In previous studies, a transcription factor was shown to regulate the expression of its own gene (39,42). To determine whether Sputcn32_0304 directly regulates the expression of its own gene and Sputcn32_0305, an electrophoretic mobility shift assay (EMSA) was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Two single mutants of Sputcn32_0304 and Sputcn32_0305, Δ0304 and Δ0305, were constructed. The deletion mutant of Sputcn32_0304 was constructed according to previous studies (39)(40)(41), which can avoid the polar effect on expression of the downstream gene Sputcn32_0303 and facilitate the investigation on its own expression changes. The biofilm biomasses of both single mutants were significantly increased compared to that of the WT strain, and biofilms of both complementation strains C-0304 and C-0305 were restored to the WT level ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation